NMR‐Assisted Molecular Docking Methodologies. Issue 8 (19th June 2015) - Sturlese, Mattia; Bellanda, Massimo; Moro, Stefano
Abstract Nuclear magnetic resonance (NMR) spectroscopy and molecular docking are regularly being employed as helpful tools of drug discovery research. Molecular docking is an extremely rapid method to evaluate possible binders from a large chemical library in a fast and cheap manner. NMR techniques can directly detect a protein‐ligand interaction, can determine the corresponding association constant, and can consistently identify the ligand binding cavity. Consequently, molecular docking and NMR techniques are naturally complementary techniques where the combination of the two has the potential to improve the overall efficiency of drug discovery process. In this review, we would like to summarize the state of the art of docking methods which have been recently bridged to NMR experiments to identify novel and effective therapeutic drug candidates.